Bone changes in polycythaemia vera and myelosclerosis. Issue 6 (November 1969) - Roberts, B. E.; Woods, C. G.; Miles, D. W.; Paterson, C. R.
Abstract : To study the problem of new bone formation in myelosclerosis bone biopsies have been performed in cases of polycythaemia vera, which may be regarded as a pre-myelosclerotic condition, and in primary myelosclerosis; morphological studies of bone and reticulin were made and osteoid and bone matrix was quantitatively assessed. Relevant metabolic studies were also carried out, but were predominantly normal. No new bone formation was detected in polycythaemia vera and some bone was osteoporotic; no significant increase in osteoid was found. With the use of polarized light it was found that new bone formation in myelosclerosis resulted from the ossification of wavy argyrophilic fibres in marrow: the presence of a dense network of these wavy fibres was a pre-requisite of new bone formation and ossification of the non-refractile branched reticulin fibres was not observed.